The end of 1 PIE chapter - Zailin Shah, Yusoff (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
21 June 2010. The Preparatory Intensive English (PIE) programme ended on June 18, 2010. The students had undergone twenty weeks of lectures as well as two Community Excursion Programmes. They sat for their final examinations from 14 till 17 of June 2010. Upon receiving their results, successful students embarked on their undergraduate studies. Registration for the new semester was on July 3, 2010.